A Comparative Study of Environmental Discourse: An Ecolinguistic Perspective - Javed, Faiqa; Nayab, Durr-e- (Annals of Human and Social Sciences, 2025)
The study comparatively examines the climate change news headlines of the UK and Pakistan. The study investigates the certain lexical choices and sentence structure of news headlines of both countries; UK and Pakistan. The study analyses the news headlines from two media channels BBC and BOL News. The primary focus of the study is to identify those structures of language used in the reporting in which some beliefs, ideologies and perspectives hold importance and others are treated unimportantly. The purpose of the study is to identify the function of language in climate change news for shaping and framing people’s mind in relation to nature and environment. Stibbe’s Theory of Ecolinguitics (2015) along with the framework of Fairclough Critical Discourse Analysis (1989/1995) is applied to this study. A purposive sampling technique is used to collect 24 news headlines from both news channels over the period 2022-23. The research follows a qualitative methodology. The findings suggest the role of different narratives like Identity, Evaluation, and Conviction in making common people believe and form ideologies. The choice of words in constructing a complete news headline serve to make language strengthening or weakening for the creation of human-nature bond. The results show contrasting discourse strategies which weakens or strengthens the relationship of man with nature. The future researcher can expand this study by deeply analysing print media and by exploring different countries through different theoretical lenses.